Sustentabilidade em estádios de futebol : o caso da Arena Pantanal em Cuiabá-MT - Pereira, Rodrigo Pinheiro Tóffano (2013)
With the expansion of great sporting events to developing countries – many of them rich in natural resources – policies for a greener architecture have become more and more recurrent once these championships demand great infrastructure constructions which inevitably impact the surrounding environment. The purpose of this paper is to verify if the designing solutions adopted in the construction of the case study, the Arena Pantanal, one of the host cities of the 2014TM XX FIFA Brazil World Cup, in Cuiabá, Mato Grosso, really shows principles of sustainability. The foundation of this paper consists of a literature review and historical review about this issue, showing the parameters and peculiarities that direct soccer stadium projects over the years. The most significant examples of large arenas projects, which included in its design sustainable actions, deserve attention and have been collected and catalogued for this research. As well as the analysis of environmental certification models, highlighting the north- american one LEEDTM, because it is required by FIFA and its standards for the organization of the last World Championships. From a critical scientific registry, based on all the theoretical background and through graphic resources, as they were indispensable, it has been done the assessment of the sustainable design solutions taken at the Arena Pantanal. As a result, it should be noted that the pursuit of a built environment, of big proportions like this one, 100% sustainable, based on ideal formulas, is impossible to be executed. However, it is indeed possible to minimize or mitigate the environmental impacts caused by the construction of a soccer stadium; through guidelines and sustainability actions which are directly related since the birth of a new project. Thus, this research is only a reference to analogue contexts, and not a model, solution or rule to be repeated in sporting constructions.